Exploring the Psychological Effects of COVID-19 Home Confinement in China: A Psycho-Linguistic Analysis on Weibo Data Pool - Wu, Peijing; Zhao, Nan; Li, Sijia; Liu, Zeyu; Wang, Yilin; Liu, Tianli; Liu, Xiaoqian; Zhu, Tingshao (Frontiers in Psychology, 2021)
Backgrounds: With the rapid spread of COVID-19, strict home confinement have been implemented in most parts of Chinese regions. Millions of people were not allowed to leave their homes except for special reasons. While it played an essential role in curbing pandemic and promoting preventive behaviors, it might have impacted individuals’ mental health as well. Objects: The objective of this study was to explore the psychological impacts of home confinement. Methods. We collected more than 150,360 Weibo messages from 5,370 Chinese active users, extracted psycho-linguistic features from these messages and applied the 2 (confinement vs non-confinement) x2 (before vs after confinement) repeated measure analysis of variance (RM ANOVA). Results: The results showed that the frequency of positive emotion words was decreased during home confinement generally (F (5370) = 7.926, p < .001). In high-endemic subgroup, home confinement also reduced the frequency of exclusion words (F (3447) = 4.518, p = .034) and inhibition words (F (3447) = 10.154, p = .001). Conclusions: Home confinement have generally caused a decline in the use of positive emotion words. This indicated that home confinement generally facilitated a decrease in positive emotion. The changes of exclusion words and inhibition words in high-endemic areas might be related to the high epidemic threat and the urgent need for social distancing in these areas.